Miniaturized Ring Resonator Wideband Bandpass Filter with Wide Stop Band - inder pal Singh; Praveen Bhatt (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
In this paper miniaturized quarter wavelength rectangular shaped multimode ring resonator bandpass filter with extended diagonal corners and internally located high impedance perturbation stubs, is proposed. Input/output open stubs are tightly coupled to the extended diagonal corners running parallel to the two sides of the ring resonator, implemented to generate wide passband and wide stop-band. Cut-off frequencies can be shifted to the higher side by increasing the length of the sides of resonator. By inserting the perturbation stubs, rectangular ring resonator produces three degenerate modes out of which first two form a wide passband. Small square patch is attached to the opposite interior corners of the ring resonator and T-shaped stub attached to the opposite longer side of the resonator are tightly coupled with feeder line to improve the return loss, insertion loss and skirt-characteristics. Shorter sides of the rectangular ring resonator are bent in U-shaped to increase the effective length of the resonator eventually the bandwidth is widened. Filter is designed and simulated for the center frequency of            3.2 GHz, bandwidth from 2.0 GHz to 4.0 GHz, on dielectric constant 3.38 and thickness 0.508 mm. Electromagnetic simulator Ansoft HFSS is used to optimize the filter dimensions.